2018
DOI: 10.1080/14686996.2018.1428478
|View full text |Cite
|
Sign up to set email alerts
|

One-step growth of thin film SnS with large grains using MOCVD

Abstract: Thin film tin sulphide (SnS) films were produced with grain sizes greater than 1 μm using a one-step metal organic chemical vapour deposition process. Tin–doped indium oxide (ITO) was used as the substrate, having a similar work function to molybdenum typically used as the back contact, but with potential use of its transparency for bifacial illumination. Tetraethyltin and ditertiarybutylsulphide were used as precursors with process temperatures 430–470 °C to promote film growth with large grains. The film sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…In Figure 3A, all the samples except sample S2‐520 exhibit the CZTS phase. The variation in the observed spectra of S2‐520 may be due to the presence of SnS (152 and 230 cm −1 ) and Sn 2 S 3 (304 cm −1 ) in the large proportion across the sample surface 41‐43 . Though there is a visible SnS secondary phase in S2 and S3 series from XRD patterns, there are no visible clues from Raman analysis.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In Figure 3A, all the samples except sample S2‐520 exhibit the CZTS phase. The variation in the observed spectra of S2‐520 may be due to the presence of SnS (152 and 230 cm −1 ) and Sn 2 S 3 (304 cm −1 ) in the large proportion across the sample surface 41‐43 . Though there is a visible SnS secondary phase in S2 and S3 series from XRD patterns, there are no visible clues from Raman analysis.…”
Section: Resultsmentioning
confidence: 98%
“…The variation in the observed spectra of S2-520 may be due to the presence of SnS (152 and 230 cm À1 ) and Sn 2 S 3 (304 cm À1 ) in the large proportion across the sample surface. [41][42][43] Though there is a visible SnS secondary phase in S2 and S3 series from XRD patterns, there are no visible clues from Raman analysis. Further, some reports suggest the peak at 160 cm À1 to be of the SnS phase, 44 but the same peak is observed in the S1 series, which is entirely devoid of the SnS phase as seen from the corresponding XRD patterns rules out the peak to be of SnS phase.…”
Section: Raman Analysis: Disorder and Phase Identificationmentioning
confidence: 99%
“…It was necessary to use a 6-fold greater concentration of t-Bu 2 S to Et 4 Sn due to the higher vapor pressure of sulfur compensating for its re-evaporation from the growing SnS film. The authors have reported [7] these optimised parameters in another article.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, H 2 S is a highly toxic gas so special measures are required for its use [6]. Ditertiarybutylsulfide (t-Bu 2 S) is an alternative sulfur source, with less toxicity than H 2 S and has been used by the authors employing the metal organic chemical vapor deposition (MOCVD) process [7]. Tetraethyltin (Et 4 Sn) was used in this study as the tin precursor with successful growth of single phase SnS on to molybdenum (Mo) substrates.…”
Section: Introductionmentioning
confidence: 99%
“…SnS is attractive because it is low-cost, non-toxic and earth-abundant. 5 SnS crystalizes in a layered orthorhombic Pnma (or equivalent Pbnm and Pmcn) structure at room temperature and undergoes a reversible transformation to a more symmetric orthorhombic Cmcm phase at around 878 K. 6,7 The high-temperature phase has been associated with strongly-anharmonic lattice dynamics and a low, intrinsic lattice thermal conductivity. 8,9 However, while SnS possesses a high Seebeck coefficient, the electrical conductivity of pure SnS is very low due to its low intrinsic carrier concentration, resulting in a low power factor.…”
Section: Introductionmentioning
confidence: 99%